2009
DOI: 10.4103/0971-6866.55221
|View full text |Cite
|
Sign up to set email alerts
|

Drugs impact on CYP-450 enzyme family: A pharmacogenetical study of response variation

Abstract: Pharmacogenetics is the study of genetic basis in the individual response to drugs. A thorough knowledge of this will lead to a future where tailor-made drugs, suiting an individual, can be used. Scandinavian countries have been known for wide usage of pharmacogenetics and the most widely used application is for genotyping CYP2D6 in treating psychiatric illness. The CYP-450 enzyme, a super family of microsomal drug-metabolizing enzymes, is the most important of enzymes that catalyzes phase-I drug metabolism re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Thus the validated method was used for analysis of PCM, TMD and DMP in their combined tablets dosage form (Brand A and B) [20][21][22][23][24][25][26][27].…”
Section: Application Of Validated Methods To Pharmaceutical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the validated method was used for analysis of PCM, TMD and DMP in their combined tablets dosage form (Brand A and B) [20][21][22][23][24][25][26][27].…”
Section: Application Of Validated Methods To Pharmaceutical Formulationmentioning
confidence: 99%
“…Literature survey revealed that various analytical methods like spectrophotometric [3][4][5][6], HPLC [7][8][9][10][11][12][13][14], GC [15] and HPTLC [16][17][18][19] have been reported for the determination of TMD, PCM and either individually or combination with some other drugs, but no HPTLC method was reported for simultaneous estimation of TMD and PCM and domperidol in combined dosage forms. Many methods [20][21][22][23][24][25][26][27] have been described in the literature for the determination of domperidol and pracetamol, individually. The analytical methods like HPLC [28] and HPTLC [29] for determination of domperidol and PCM in combined dosage form have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…45 For example, SULT1A1 polymorphism is associated with an increased risk of some cancers, such as breast cancer (especially in Asian patients), 46 gastric cancer, 47 tongue cancer in women, 48 and oral squamous cell carcinoma in Taiwanese patients with the H149Y haplotype. 49 CYP450s are critical in the stimulation of phase I drug metabolism 50 and detoxification as well as the elimination of common drugs. 51 CYP450 polymorphism can affect the efficacy and side effects of drugs.…”
Section: Adrs and Pharmacogenomicsmentioning
confidence: 99%
“…It is used to treat moderate to moderately severe pain and most types of neuralgia, including trigeminal neuralgia. Literature survey reveals that, several spectrophotometric method [1][2][3] TLC-densitometry 4 , UV spectrophotometric and HPLC-DAD RESEARCH ARTICLE methods 5 , HPLC method [6][7][8] High Performance thin layer chromatography-densitometry 9 , have been reported for the estimation of tramadol in pharmaceutical formulations. Few analytical methods were reported in literature for the determination of tramadol and other combination drugs which includes spectrophotometric method [10][11][12][13][14][15][16] , spectrophotometric and spectrofluorimetric method 17 .…”
Section: Introductionmentioning
confidence: 99%